Diplomacy from Internacional networking in Higher Education: Biometric analysis of the case “Interleader” (Revista Electrónica Calidad en la Educación Superior, 2023)
The analysis of international academic networks allows us to reflect on the functioning of cooperative societies of research and academic professionals. The theory of academic diplomacy and the intersection between international relations and education is responsible for this.Through this theoretical approach and under the logic of a case study, the Network for Research and Practice in Educational Leadership is analyzed revealing the most representative milestones of its formation in the academic field, where however, newer challenges were found. Results, show how academic networks, higher education, internationalization, diplomacy are factors of a globalization of knowledge
Keywords: Academic Diplomacy; Reserch Network; Educational Internalization; Proffesional Community; Science Divulgation